2018
DOI: 10.26444/aaem/80984
|View full text |Cite
|
Sign up to set email alerts
|

Badgers as a potential source of bovine tuberculosis – first studies in Poland

Abstract: Since 2009, Poland has been recognized as a country officially free of bovine tuberculosis (BTB). However, new outbreaks are each year quoted. In many countries it has been shown that badgers (Meles meles) are a vector of Mycobacterium bovis/caprae (M.bovis/caprae) and a source of bovine tuberculosis for many domestical species, mainly for cattle. The aim of the presented study was to determine, for the first time in Poland, the occurrence of tuberculosis in badgers in areas where the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In Poland, the bovine mycobacteria reservoir is cattle suffering from tuberculosis. Unlike in the United Kingdom, the Polish badger population is not a reservoir of M. bovis and is free of infection (21). Identified spoligotypes of Polish strains are commonly found in Europe (5,18) and the most common spoligotype in these studies, SB2220 according to the Mbovis.org database, was isolated for the first time in Iran in 2013, which is also demonstrative of international transmission.…”
Section: Discussionmentioning
confidence: 82%
“…In Poland, the bovine mycobacteria reservoir is cattle suffering from tuberculosis. Unlike in the United Kingdom, the Polish badger population is not a reservoir of M. bovis and is free of infection (21). Identified spoligotypes of Polish strains are commonly found in Europe (5,18) and the most common spoligotype in these studies, SB2220 according to the Mbovis.org database, was isolated for the first time in Iran in 2013, which is also demonstrative of international transmission.…”
Section: Discussionmentioning
confidence: 82%
“…For example, in the UK, and probably in the Republic of Ireland, the reservoir of M. bovis are badgers [25,26]. Preliminary studies conducted by Lipiec and others prove that in Poland the badger population is free from bTB infections [27].…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, a pilot study on the prevalence of TB in various animal populations was carried out by Lipec et al ( 2018) and ; however, its presence in badgers and sheep has not been confirmed [14,22,23], even though TB has been found to cause deaths in these species in other countries [24,25,26,27]. Surprisingly, MTBC were not isolated from deer from the Bieszczady region (Podkarpackie Province), where TB has been identified in wildlife.…”
Section: Discussionmentioning
confidence: 99%